Theorizing the standoff : contingency in action - Wagner-Pacifici, Robin Erica (Cambridge cultural social studies., 2000)
This book combines original theoretical analysis with real life case studies to examine the nature of the standoff. The author explores the archetypal patterns of human action and cognition that move us into and out of these highly charged situations and seeks to theorize the contingency of all such moments.